Expression of therapy target molecules in esophagogastric junction and Barrett’s adenocarcinoma - Abe, Hiroyuki; Urabe, Masayuki; Yagi, Koichi; Yamashita, Hiroharu; Seto, Yasuyuki; Ushiku, Tetsuo (Gastric cancer : official journal of the International Gastric Cancer Association and the Japanese Gastric Cancer Association, 2025)
Background Recently, novel molecular targeted therapies have been developed for gastric and esophageal adenocarcinomas. We examined the status of therapeutic target molecules in esophagogastric junction (EGJ) and Barrett’s adenocarcinoma. Methods Tissue microarrays were constructed from 114 cases of non-Barrett’s EGJ adenocarcinoma and 30 cases of Barrett’s adenocarcinoma. Immunohistochemistry for mismatch repair proteins, PD-L1, HER2, CLDN18, FGFR2b, and EBER-ISH was performed. When HER2 immunohistochemistry was 2 + , gene amplification was examined using in situ hybridization. Results EBER positivity, mismatch repair deficiency, PD-L1 combined positive score (CPS) ≥ 1, CLDN18 expression ≥ 75%, FGFR2b expression, and HER2 positivity were observed in 7 (6.1%), 11 (9.6%), 70 (61.4%), 38 (33.3%), 6 (5.3%), and 11 (9.6%) cases of EGJ adenocarcinoma as well as in 0 (0%), 0 (0%), 23 (76.7%), 7 (23.3%), 2 (6.7%), and 6 (20.0%) cases of Barrett’s adenocarcinoma, respectively. PD-L1 CPS ≥ 1 cases had longer recurrence-free survival ( P = 0.001) and overall survival ( P = 0.003) than CPS < 1 cases. Other target molecules were not associated with survival. A total of 93/114 (81.6%) cases of EGJ adenocarcinoma and 26/30 (86.7%) cases of Barrett’s adenocarcinomas expressed at least one target molecule. Conclusions Most EGJ and Barrett’s adenocarcinomas may be eligible for molecular targeted therapy. Appropriate patient stratification based on these molecular tests will be important for precision medicine of the EGJ and Barrett’s adenocarcinoma.